2011
DOI: 10.1080/19325037.2011.10599175
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Comprehensive Heart Disease Knowledge Questionnaire

Abstract: Background Heart disease is the number one killer of both men and women in the United States, yet a comprehensive and evidence-based heart disease knowledge assessment is currently not available. Purpose This paper describes the 2 phase development of a novel heart disease knowledge questionnaire. Methods After review and critique of the existing literature, a questionnaire addressing 5 central domains of heart disease knowledge was constructed. In Phase I, 606 undergraduates completed a 82-item questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 48 publications
0
52
2
3
Order By: Relevance
“…1e79). Before prevention programs and policies can be developed, the gap between CV risk factors and CVD knowledge has to be determined (Bergman et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1e79). Before prevention programs and policies can be developed, the gap between CV risk factors and CVD knowledge has to be determined (Bergman et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the study the term CVD knowledge refers to the information that an individual has about CVD, and the possible risk factors contributing to the development of CVD. CV risk factor knowledge are very important for making decisions about health (Bergman et al, 2011).…”
Section: Cvd Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that recent studies involving the development of new questionnaires are following these steps (Farias et al, 2008;Buysse et al, 2010;Bergman et al, 2011;Giesler et al, 2011;Marant et al, 2011;Young et al, 2011). These studies showed the steps of literature review on the topic being discussed and literature review on other scales that could be used for the same purpose.…”
Section: A Description Of All Steps For Developing a New Measuring Inmentioning
confidence: 99%
“…These studies showed the steps of literature review on the topic being discussed and literature review on other scales that could be used for the same purpose. Furthermore, some researchers consulted experts with experience on the area of interest during the selection of domains and items (Farias et al, 2008;Bergman et al, 2011); others conducted focus groups and semi-structured interviews to obtain relevant information for the generation of items (Buysse et al, 2010;Young et al, 2011); and others have conducted interviews with a sample of the target population in order to obtain important suggestions during the developing of the conceptual model of the questionnaire (Giesler et al, 2011;Marant et al, 2011).…”
Section: A Description Of All Steps For Developing a New Measuring Inmentioning
confidence: 99%